Study on High Activity and Outstanding Stability of Hollow-NiPt@SiO2 Core–Shell Structure Catalyst for DRM Reaction - Wang, Guangying; Liang, Yan; Song, Jian; Li, Hui; Zhao, Yu (Frontiers in Chemistry, 2020)
A neoteric hollow-NiPt@SiO2 core–shell structure catalyst with 7-nm-sized hollow NiPt alloy nanoparticle (NP) packaged by SiO2 shell was prepared by a classic Stober method. Compared with hollow-NiPt/SiO2 supported catalyst, the hollow-NiPt@SiO2 core–shell catalyst exhibited better activity and thermal stability in dry reforming of methane (CH4) (DRM) with CO2 reaction, with CH4/CO2 conversion to 97% and service life to 200 h at 800°C, respectively. In addition, the activity and stability of core–shell catalysts with different nuclei were tested. In contrast to the continuous deactivation of the supported catalyst, all the core–shell catalysts were able to maintain stability for 200 h, and the activity sequence was Hollow-NiPt > NiPt NPs > Pt NPs > Ni NPs. By characterization, we learned that hollow structure had an inner surface and thus had a larger active specific surface area than NP structure. In addition, NiPt NPs had better activity than Ni NPs and Pt NPs because Ni and Pt formed as alloy in NiPt NPs. Therefore, the efficient and thermally stable hollow-NiPt@SiO2 core–shell catalyst has a promising application prospect in DRM reaction and can make a considerable contribution to the sustainable use of energy.